Molecular characterization, expression patterns and cellular localization of BCAS2 gene in male Hezuo pig - Tang, Yuran; Zhang, Bo; Shi, Haixia; Yan, Zunqiang; Wang, Pengfei; Yang, Qiaoli; Huang, Xiaoyu; Gun, Shuangbao (PeerJ, 2023)
Background Breast carcinoma amplified sequence 2 (BCAS2) participates in pre-mRNA splicing and DNA damage response, which is implicated in spermatogenesis and meiosis initiation in mouse. Nevertheless, the physiological roles of BCAS2 in the testes of large mammals especially boars remain largely unknown. Methods In this study, testes were collected from Hezuo pig at three development stages including 30 days old (30 d), 120 days old (120 d), and 240 days old (240 d). BCAS2 CDS region was firstly cloned using RT-PCR method, and its molecular characteristics were identified using relevant bioinformatics software. Additionally, the expression patterns and cellular localization of BCAS2 were analyzed by quantitative real-time PCR (qRT-PCR), Western blot, immunohistochemistry and immunofluorescence. Results The cloning and sequence analysis indicated that the Hezuo pig BCAS2 CDS fragment encompassed 678 bp open reading frame (ORF) capable of encoding 225 amino acid residues, and possessed high identities with some other mammals. The results of qRT-PCR and Western blot displayed that BCAS2 levels both mRNA and protein were age-dependent increased (p < 0.01). Additionally, immunohistochemistry and immunofluorescence results revealed that BCAS2 protein was mainly observed in nucleus of gonocytes at 30 d testes as well as nucleus of spermatogonia and Sertoli cells at 120 and 240 d testes. Accordingly, we conclude that BCAS2 is critical for testicular development and spermatogenesis of Hezuo pig, perhaps by regulating proliferation or differentiation of gonocytes, pre-mRNA splicing of spermatogonia and functional maintenance of Sertoli cells, but specific mechanism still requires be further investigated.
Keywords: Hezuo pig; BCAS2; Molecular characterization; Testicular development; Spermatogenesis